The Study of Gay Slang in Bungus Teluk Kabung Padang - Natalion Nanda Putra; Mac Aditiawarman (Jurnal Ilmiah Pendidikan Scholastic, 2019)
This research is sociolinguistics study of slang used by the gay in Padang which focuses on the use of slang especially in Bungus Teluk Kabung. This research using Wardhaugh and Holmes theory about varieties of language. The objectives of this research are (1) To identify the slang word employed by gay in Padang (2) To analyze the social context of the use of slang words in Padang (3) To reveal the reason why they use slang words. This research used descriptive qualitative and quantitative approach that is the research produces analytical procedures that do not use statistical analysis procedure. The source of data in this study is the gay conversation in Padang especially in Bungus, while the data in the form of words or diction derived from gays” utterances. The data in this study was collected by using the voice recording technique then they were classified and analyzed. The trustworthiness was attained by using credibility through two kinds of triangulation: by observes and theories. The results of the research show three points. First, there are three types of gay slang employed by gay in Bungus that are offensive type, vulgar type, and taboo type. Second, the social context of slang use by gay in Padang. Third, the reason why they use slang. Based-on record strategy has the highest frequency among other strategies since the dialogues are among gay Bungus members who have a close relationship and know each other very well. And the next, the function of the study of gay slang in Bungus it teaches how to use the slang language and have the conversation go well and run smoothly. As a conclusion, the study of gay slang are the way to analyze some types of slang language in gay Bungus, social context, and to know the reason why they use that slang.